Enhanced intercropping productivity of sweet corn-okra in young rubber plantation - Samsuri, Shampazuraini (2022)
Rubber smallholders as a group is the most important player in the Malaysian rubber industry. During the early five year period, rubber smallholders have no source of income due to the long gestation period before the rubber trees can be tapped. However, rubber smallholders can generate income by practicing intercropping of rubber with food crops before the canopy closure of the rubber trees. In this regard, two seasons of field studies were conducted at the Rubber Research Institute of Malaysia Mini Station (RRIMINIS) Jasin, Melaka. The objectives were to evaluate the growth and yield performances, physiological characteristics, efficiency parameters and economic potential of sweet corn and okra intercropping planted in the young rubber plantation. Study 1 was carried out in November 2019 and the treatments were arranged in a randomized complete block design (RCBD) with three replications. The treatments comprised of five different sweet corn-okra intercropping ratios: T1 (20% okra + 80% sweet corn + rubber), T2 (50% okra + 50% sweet corn + rubber), T3 (80% okra + 20% sweet corn + rubber), T4 (100% okra + rubber) and T5 (100% sweet corn + rubber). Results on sweet corn revealed that the number of marketable cobs (31,999), cob yield (9,845 kg ha-1) and biomass yield (32,816 kg ha-1) were significantly influenced by the intercropping ratio where the highest value was obtained in sole sweet corn planting. Growth and yield of okra were significantly reduced when okra was intercropped with sweet corn. Maximum leaf area index (LAImax) and maximum crop growth rate (CGRmax) showed significant difference of okra in all intercropping ratios but almost similar to sweet corn. The crop total intercepted photosynthetically active radiation (PAR) varied in different intercropping ratios and the highest was achieved by sole sweet corn and okra. For intercropping efficiency, the highest land equivalent ratio (LER) and monetary advantage index (MAI) were from the intercropping ratio of T1 with 1.14 and RM 3,388 ha-1, respectively. Moreover, the economic analysis indicated that T1 also was the most profitable with the highest gross margin (RM 13,668.50 ha-1). Study 2 was conducted in September 2020 at the same plot with a different intercropping system. The experimental design was RCBD with three replications. Intercropping ratio of 20% okra + 80% sweet corn was chosen from Study 1 and sole okra and sweet corn were used as controls. The study consisted of T1 (strips intercropping), T2 (strip relay intercropping), T3 (sole okra) and T4 (sole sweet corn). The highest yield of okra was obtained from strip relay intercropping when sweet corn was planted 4 weeks after okra. However, the economic analysis showed that strip intercropping recorded the maximum gross margin with RM 17,733.20 ha-1. A highly significant difference was observed in the radiation use efficiency (RUE) of okra in all evaluated treatments. Strip intercropping not only resulted in the highest LER (1.29) but also area time equivalent ratio (ATER), % land saved and MAI with 1.14, 22.28% and RM 7,583.50 ha-1, respectively compared with strip relay intercropping. Furthermore, strip intercropping indicated the lowest competitive ratio (CR). Intercropping of rubber trees with sweet corn and okra was beneficial in the early stages of rubber growth and did not have an adverse effect on the growth and development of young rubber trees. Result revealed that the girth increment rate of young rubber trees was significantly higher for young rubber trees grown in association with sweet corn-okra in an intercropping system than for those planted without intercropping. However, stem girth and average canopy diameter of young rubber trees were not significantly affected by either with or without sweet corn-okra intercropping. Thus, the intercropping ratio of 20% okra + 80% sweet corn + rubber and under strip intercropping system were proven to be the most effective systems and highest in profitability. Intercropping can provide early income and increase land-use efficiency without neglecting the growth performances and development of the main crop of rubber itself.